Fabrication of a Simultaneous Highly Transparent and Highly Hydrophobic Fibrous Films - Doo-Hyeb Youn; Kyu-Sung Lee; Sun-Kyu Jung; Mangu Kang (Applied Sciences, 2021)
This paper discusses the fabrication and characterization of electrospun nanofiber scaffolds made of polystyrene (PS). The scaffolds were characterized in terms of their basis material molecular weight, fiber diameter distribution, contact angles, contact angle hysteresis, and transmittance. We propose an aligned electrospun fiber scaffold using an alignment tool (alignment jig) for the fabrication of highly hydrophobic (θW > 125°) and highly transparent (T > 80.0%) films. We fabricated the alignment jig to align the electrospun fibers parallel to each other. The correlation between the water contact angles and surface roughness of the aligned electrospun fibers was investigated. We found that the water contact angle increased as the surface roughness was increased. Therefore, the hydrophobic properties of the aligned electrospun fibers were enhanced by increasing the surface roughness. With the change in the electrospinning mode to produce aligned fibers rather than randomly distributed fibers, the transmittance of the aligned electrospun fibers increased. The increase in the porous area, leading to better light transmittance in comparison to randomly distributed light scattering through the aligned electrospun fibers increased with the fibers. Through the above investigation of electrospinning parameters, we obtained the simultaneous transparent (>80%) and hydrophobic (θW > 140°) electrospun fiber scaffold. The aligned electrospun fibers of PS had a maximum transmittance of 91.8% at the electrospinning time of 10 s. The water contact angle (WCA) of the aligned electrospun fibers increased from 77° to 141° as the deposition time increased from 10 s to 40 s. The aligned fibers deposited at 40 s showed highly hydrophobic characteristics (θW > 140°).